2022
DOI: 10.21831/cp.v41i2.43233
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ willingness to change in adapting to online learning during the covid-19 pandemic

Abstract: This study aimed to highlight the view of educators on the teachers’ willingness to change in adapting to online learning due to the Coronavirus disease 19 (COVID -19) pandemic. The sudden shifting required readiness to facilitate both synchronous and asynchronous learning interactions. The results of previous studies on the dissatisfaction with the online learning quality during the pandemic triggered this study. Teachers preferred to use task-based learning and resisted incorporating technology in the learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…The overall findings suggesting very high work engagement, however, may suggest that the Indonesian high school teacher participants had perseverance in teaching despite the challenges. This finding was in line with the finding of a previous study by Herawati et al, (2021) in Indonesia. They reported that their teacher participants were willing to adapt to the rapid changes due to the pandemic and update their knowledge to overcome challenges.…”
Section: High School Teachers' Level Of Work Engagement In the Teachi...supporting
confidence: 93%
See 3 more Smart Citations
“…The overall findings suggesting very high work engagement, however, may suggest that the Indonesian high school teacher participants had perseverance in teaching despite the challenges. This finding was in line with the finding of a previous study by Herawati et al, (2021) in Indonesia. They reported that their teacher participants were willing to adapt to the rapid changes due to the pandemic and update their knowledge to overcome challenges.…”
Section: High School Teachers' Level Of Work Engagement In the Teachi...supporting
confidence: 93%
“…The process of acquiring new knowledge in IT was manifested in their willingness to try what they had learned. Herawati et al (2021) further found that the teacher participants had a sense of openness, were aware of the need to implement IT and had the willingness to continuously update their knowledge to overcome challenges.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hence, this possibly made the item 'The suitability of the feedback given by the lecturer in learning' (4.32) and 'Lecturer's concern for student difficulties' (4.30) score lower as the teacher failed to identify the emerging emotions and feelings when something went wrong. This willingness to integrate technology for distance learning has been further investigated by Herawati et al (2022). They argue that willingness to change is a new predictor of professional development in establishing quality instruction.…”
Section: Reflection On Ite's Pedagogical Competencesmentioning
confidence: 99%